(untitled) (Scientific journal of the Fergana State University, 2023)
In Uzbekistan, serious attention is paid to the involvement of girls in sports activities, and strict action plans have been developed for this purpose. Programs in various areas of sports were adopted and put into practice. Also, in order to create wider opportunities for schoolgirls to participate in the Olympic movement, a commission on women and sports was established under the National Olympic Committee.